Survey of Consumer Attitudes and Behavior, Winter 1976 ([Verlag nicht ermittelbar], 1984)
This survey was undertaken to assess consumer sentiment and buying plans as well as views on price fluctuations. Open-ended questions were asked concerning evaluations and expectations about personal finances, employment, recession, price changes, and the national business situation. Additional variables probe respondents' buying intentions for a house, automobiles, appliances, and other consumer durables, and respondents' appraisals of present market conditions for purchasing houses and other durables. Other variables probe respondents' assessments of their financial status relative to the previous year, their satisfaction with their savings, and their opinions on penalties for marijuana use, public speeches against democracy, communism and free speech, degree of government control of local education, causes of crime and lawlessness, gun permit law, public officials' responsiveness to public opinion, United States' intervention in the world's trouble spots, the comparative effect of a Democratic president and a Republican president on the economy, air pollution, and the relative value of small and standard full-size cars. Information is also provided on respondents' monetary debts, previous and future planned vacation trips, and car ownership and the plans to buy a new one. Demographic variables provide information on respondents' age, sex, race, marital status, education, occupation, employment status, and income.